PENGGUNAAN OBAT GOLONGAN PROTON PUMP INHIBITTOR PADA PASIEN RAWAT INAP DI RUMAH SAKIT PKU MUHAMMADIYAH GAMPING YOGYAKARTA - Sari, Chynthia Pradiftha; Rachman, Chintia Khairunnisa; Hanifah, Suci; Mutmainah, Isti (Universitas Borneo Lestari, 2024)
Proton pump inhibitor (PPI) is a drug with a good safety profile and effectiveness for patients with various conditions, so it is routinely prescribed around the world, one of them at PKU Muhammadiyah Gamping Yogyakarta. The aim of this study is to find out the profile of PPI drug use and the appropriate doses of the PPI group of drugs in hospitalized patients. This study is a descriptive observational study with a cross-sectional design. Data collection through secondary data is 200 patient medical records retrospectively. The results of the study showed the highest diagnosis of PPI drug use for gastro (60.50%) and non-gastro (39.50%). There are drugs that are given to patients at risk of gastrointestinal bleeding: NSAIDs (88.4%), glucocorticosteroids (8.97%), and anticoagulants (2.56%). The types of PPI used are pantoprazole injections 40 mg, lansoprazole tablets 30 mg, and lansoprazole injections 30 mg. The accurate dosage appropriate of PPI use is 100%.